2010
DOI: 10.1016/j.rmed.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of COPD patients requiring frequent hospitalization: Role of airway infection

Abstract: Airway infection by non-usual pathogens appears to be a key driver of frequent hospitalizations and mortality in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
4
21
0
2
Order By: Relevance
“…These figures were similar to those reported in previous studies in patients with advanced disease, as shown by Murphy et al [30] and Renom et al [9], who reported P. aeruginosa isolation in over one third of the sputum samples obtained from COPD patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These figures were similar to those reported in previous studies in patients with advanced disease, as shown by Murphy et al [30] and Renom et al [9], who reported P. aeruginosa isolation in over one third of the sputum samples obtained from COPD patients.…”
Section: Discussionsupporting
confidence: 92%
“…Two studies [4,5] have shown that individuals with a FEV1 below 50% of the reference level have a six-fold higher risk of suffering exacerbations due to H. influenzae and P. aeruginosa than patients with mild or moderate COPD. Likewise, P. aeruginosa infection in COPD has also been related to risk factors such as previous hospital admissions and use of oral corticosteroids or antibiotics [6-9] but the importance of these individual determinants has not been elucidated. Moreover, the role of other potential factors such as bronchiectasis, as a risk factor of P. aeruginosa in cursive infection-a factor associated with severe airflow obstruction in COPD [10], has been addressed only marginally [8].…”
Section: Introductionmentioning
confidence: 99%
“…Two main reasons may account for this finding. First, it may be related to the fact that COPD patients more frequently received antibiotics before admission, and this has been shown to be protective against severe CAP [17,18]. Accordingly, it has also been demonstrated in a large series of 388,406 CAP patients in Germany that death occurs most frequently within the first day after admission [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another more recent prospective publication performed in 116 ambulatory patients with severe disease obtained similar results. However, the data reported by the authors suggest that the study was conducted in a highly selected population with up to 71% of patients with nonusual flora, mainly PA and Enterobacteriaceae [25]. …”
Section: Discussionmentioning
confidence: 99%